Field report spring 1995, Thomas Kent - Kent, Thomas H. (Thomas Hugh), 1934-et al (1995)
An annotated list of birds sighted by Thomas Kent dated June 1, 1995. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1995. Epson - sheet feed